A diverse uncultivated microbial community is responsible for organic matter degradation in the Black Sea sulphidic zone. (13th January 2020) - Suominen, Saara; Dombrowski, Nina; Sinninghe Damsté, Jaap S.; Villanueva, Laura
Summary: Organic matter degradation in marine environments is essential for the recycling of nutrients, especially under conditions of anoxia where organic matter tends to accumulate. However, little is known about the diversity of the microbial communities responsible for the mineralization of organic matter in the absence of oxygen, as well as the factors controlling their activities. Here, we determined the active heterotrophic prokaryotic community in the sulphidic water column of the Black Sea, an ideal model system, where a tight coupling between carbon, nitrogen and sulphur cycles is expected. Active microorganisms degrading both dissolved organic matter (DOM) and protein extracts were determined using quantitative DNA stable isotope probing incubation experiments. These results were compared with the metabolic potential of metagenome‐assembled genomes obtained from the water column. Organic matter incubations showed that groups like Cloacimonetes and Marinimicrobia are generalists degrading DOM. Based on metagenomic profiles the degradation proceeds in a potential interaction with members of the Deltaproteobacteria and Chloroflexi Dehalococcoidia . On the other hand, microbes with small genomes like the bacterial phyla Parcubacteria, Omnitrophica and of the archaeal phylum Woesearchaeota, were the most active, especially in protein‐amended incubations, revealing the potential advantage of streamlined microorganisms in highly reduced conditions.